APPLICATION OF THE MATRIX METHOD IN ECONOMIC MODELING - Savić, Aleksandar; Ristić, Dejan; Mičić, Saša (International Journal of Economic Practice and Policy, 2024)
The matrix method for designing models is common and widely applied in various fields of economics. Matrix methods in economic modelling can generally be in a form of linear algebraic equations or equivalent representations. The process of defining certain assumptions and adopting the model is done by formulation. It includes breaking down the problem and defining the steps in which the problem will be solved. Matrix programming methods represent a class of optimization economic models because their goal is to find optimal solutions to problems. For a complex analysis of the economic structure and interconnection of individual parts of the economy, flows, and reproduction processes, intersectoral (input-output) tables provide the necessary statistical and informational basis. The cross-sector matrix (input-output) models allow a deeper insight into the structure and interdependence of individual economic processes. In this context, the main goal of this paper is to show the importance of applying the matrix method in economic science because its correct application can reduce many ambiguities, both in economic theory and in practice.
Keywords: business management; activity classification; cross-sectoral tables; national accounts